Pengetahuan Ibu Tentang Pertumbuhan Berhubungan dengan Status Gizi Anak Usia 0-59 Bulan di Wilayah Kerja Puskesmas Banguntapan I Bantul, Yogyakarta - Rikardus Nendi Irwanto; Sulistiyawati Sulistiyawati; Prastiwi Putri Basuki (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
One of the stated goals of MDGs is to eradicate extreme poverty and hunger. The higher the poverty and hunger of a country will have an impact on the health, welfare and food consumption of malnourished people, especially in toddlers. Nutrition necessity is main concern that must be considered in their growth. Nutrition can determine the level of children’s health. Good growth is not only physical growth but also their mental and intellectual development that is also expected to develop well. Therefore it becomes prevalent growth. The purpose of study was to know the relationship between mother’s knowledge on growth and children’s nutrient status aged 0-59 months in working area of Puskesmas Banguntapan I Bantul. The method was descriptive analytical research using cross sectional design and data research analysis of spearman rho. The sample collection was cluster sampling with lottery. Results showed that mother’s knowledge on growth was in good category 55.1% and less category 3.4%. Meanwhile, the nutrient status of children at age 0-59 months was in good category 70.8% and very thin category 3.4%. In conclusion, there was a relationship between mother’s knowledge on growth and children’s nutrient status aged 0-59 months in working area of Puskesmas Banguntapan I Bantul (p-value=0,000).